Kepemimpinan Transformasional Walikota Makassar (2014-2019) pada Program Makassar Tidak Rantasa (MTR) - Muhammad Ahsan Samad; Rudi Hardi (Jurnal Ad'ministrare, 2018)
This study discusses transformational leadership, the reference theory used in this study is Yukl (2007), a Professor from the State University of New York, he mapped that transformational leadership basically has four characteristics, namely; (1) ideal influences, (2) inspirational motivation, (3) intellectual stimulation, and (4) individual attention. The concept is then tested to the flagship program of Makassar's mayor elected 2014-2019 namely, Makassar Green and Clean, to make it happen a derivative program that is Makassar No Rantasa (MTR). Through qualitative approach with case study method, the researcher then get the data in more depth. Data collection was done in three ways: interview, observation and documentation study. Based on the results of the research indicates that the level of community satisfaction and government apparatus towards this program has shown positive trend, in the sense that they (the community and government apparatus) have felt the positive impact of this program, that is with the changing of environment condition and citizen mindset for cleanliness and arrangement of beauty hallway. But it can not be denied that this program has not been implemented with the maximum in all corners of Makassar, this is evidenced by the results of research in sub-district locations located on the outskirts of the city seen not getting the maximum attention from the city government.